Literature Review: Smart Trash Bin Innovation Based on The Internet of Things - Muhammad Iqbal Gymnastiar; Coki Sanjaya; Wisnu Adi Prasetyanto (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Waste management is an increasingly pressing global challenge. Smart trash cans based on the Internet of Things (IoT) offer a solution by utilizing technology to enhance the efficiency and effectiveness of waste management. However, there are still several research areas that have not been thoroughly explored, such as the use of AI and Machine Learning technology in predicting waste disposal patterns, managing specific types of waste, and integrating smart trash cans with city-wide waste management systems. Further exploration in these areas can assist in the development of smarter and more effective trash cans, positively impacting the environment and community welfare. Therefore, further research is crucial to continue optimizing this technology and creating more sustainable waste management solutions.